Effectiveness and safety of anti-TNF therapy for inflammatory bowel disease in liver transplant recipients for primary sclerosing cholangitis: A nationwide case series. Issue 7 (July 2018) - Altwegg, Romain; Combes, Roman; Laharie, David; De Ledinghen, Victor; Radenne, Sylvie; Conti, Filomena; Chazouilleres, Olivier; Duvoux, Christophe; Dumortier, Jérôme; Leroy, Vincent; Treton, Xavier; Durand, François; et al.
Abstract: Background: There is a lack of consensus regarding the treatment of inflammatory bowel disease (IBD) after liver transplantation (LT) forprimary sclerosing cholangitis (PSC). Aim: To investigate the safety and effectiveness of anti-TNF therapy in patients with IBD after a LT for PSC. Methods: We reviewed the medical files of all of the IBD patients who underwent a LT for PSC and who were treated with anti-TNF therapy at 23 French liver transplantation centers between 1989 and 2012. Results: Eighteen patients (12 with ulcerative colitis and 6 who had Crohn's disease) were recruited at 9 LT centers. All of these patients received infliximab or adalimumab following their LT, and the median duration of their anti-TNF treatment was 10.4 months. The most frequent concomitant immunosuppressive treatment comprised a combination of tacrolimus and corticosteroids. Following anti-TNF therapy induction, a clinical response was seen in 16/18 patients (89%) and clinical remission in 10 (56%). At the end of the anti-TNF treatment or at the last follow-up examination (the median follow-up was 20.9 months), a clinical response was achieved in 12 patients (67%) and clinical remission in 7 (39%). A significant endoscopic improvement was observed in 9 out of 14 patients and a complete mucosal healing in 3 out of 14 patients (21%). Six patients experienced a severe infection. These were due to cholangitis, cytomegalovirus (CMV) infection, Clostridium difficile, cryptosporidiosis, or Enterococcus faecalis . Three patients developed colorectal cancer after LT, and two patients died during the follow-up period. Conclusions: Anti-TNF therapy proved to be effective for treating IBD after LT for PSC. However, as 17% of the patients developed colorectal cancer during the follow-up, colonoscopic annual surveillance is recommended after LT, as specified in the current guidelines.